(untitled) (Journal of Buffalo Science, 2025)
The aims of the study were to determine the pregnancies and embryonic losses following Timed Artificial Insemination (TAI) protocols and to generate strategic breeding management for buffaloes. In Study 1, buffaloes in natural estrus were inseminated, serving as Control (T1). In T2, buffaloes were subjected to the Controlled Internal Drug Release-Synch-human Chorionic Gonadotropin (CIDR-Synch-hCG) protocol. In T3, animals were subjected to Prostaglandin protocol, and T4 is similar to T3 except that hCG was supplemented on the Day of AI. In Study 2, buffaloes were subjected to the CIDR-Synch-hCG protocol, and the sizes of pre-ovulatory follicles were measured as the basis for the conduct of TAI. In Study 3, animals were similarly subjected to the CIDR-Synch-hCG protocol at different seasons. Results in Study 1 indicate that the CIDR-Synch-hCG protocol achieved pregnancy rates on Days 30 and 60 post-AI and embryonic loss, which are not significantly different (P<0.05) from those of natural estrus (T1), and that the Prostaglandin protocol supplemented with hCG (T4) resulted in significantly higher pregnancies and lower embryonic loss compared with Prostaglandin alone (T3) group. In Study 2, inseminating buffaloes with ≥12.0 mm pre-ovulatory follicle size (T3) yielded the highest pregnancies (P<0.05) at Days 30 and 60 with the lowest (P<0.05) embryonic loss among follicle size groups. In Study 3, TAI performed during January-March and October-December indicated significantly higher pregnancies (P<0.05) with lower embryonic loss (P<0.05) compared with the April-June and July-September seasons. In sum, the present study demonstrated the efficiencies of Timed AI protocols, which provided opportunities for their strategic use in breeding programs to achieve greater productivity and profitability from buffalo farming.